2018
DOI: 10.1021/jacs.8b06458
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Interrogation of Co/Ni-Dual Catalyzed Hydroarylation

Abstract: Cobalt/nickel-dual catalyzed hydroarylation of terminal olefins with iodoarenes builds complexity from readily available starting materials, with a high preference for the Markovnikov (branched) product. Here, we advance a mechanistic model of this reaction through the use of reaction progress kinetic analysis (RPKA), radical clock experiments, and stoichiometric studies. Through exclusion of competing hypotheses, we conclude that the reaction proceeds through an unprecedented alkylcobalt to nickel direct tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(167 citation statements)
references
References 134 publications
5
158
1
3
Order By: Relevance
“…These ideas have spurred our labs interest in using a homogeneous silane based reductant in nickel mediated RASS‐based cross couplings . We found the Ni/silane system in DMA to be flexible in its utility.…”
Section: Figurementioning
confidence: 99%
“…These ideas have spurred our labs interest in using a homogeneous silane based reductant in nickel mediated RASS‐based cross couplings . We found the Ni/silane system in DMA to be flexible in its utility.…”
Section: Figurementioning
confidence: 99%
“…Meanwhile, Schenvi and coworkers successfully extended the hydrofunctionalization to a Co‐catalyzed branch‐selective hydroarylation for the cross‐coupling of iodoarenes with alkenes in the presence of hydrosilane (Scheme ) . Mechanistic studies revealed that the cross‐coupling proceeds via a cage‐rebound process between alkyl‐Co(III) and aryl‐Ni(III) complexes within a solvent cage . Thus, a SET process from secondary alkyl‐Co(III) intermediate 77 to aryl‐Ni(III) 78 would provide alkyl‐Co(IV) intermediate 79 and aryl‐Ni(II) 80 .…”
Section: Planar Co(iii)‐hydride Complexesmentioning
confidence: 99%
“…[15][16][17] Our group previously reported aC o/Ni bimetallic hydroarylation of olefins,w here Co(Sal t-Bu,t-Bu )BF 4 appeared to be superior to Co(Sal t-Bu,t-Bu )Cl. [18,19] We found that at high dilution Co(Sal t-Bu,t-Bu )BF 4 catalyzes cycloisomerization significantly faster than the initially reported Co(Sal t-Bu,t-Bu )Cl. Water, however,h ad al eveling effect on this cationic complex, possibly acting as an apical ligand, so that both complexes reached roughly equal rates ( Figure 2).…”
Section: Resultsmentioning
confidence: 83%
“…Indeed, we have found N-fluorocollidinium oxidants to rescue off-pathway Co +2 species by reoxidation to Co +3 . [18] Importantly,r ates at high dilution (1 mm) allowed completion of the reaction within only 25 minutes. Initial rates indicated the bimolecular MHATs tep (Path 1, Figure 4) must possess ar ate constant of at least 76 m À1 s À1 , corresponding to an energy barrier of at most 14.9 kcal mol À1 .…”
Section: Angewandte Chemiementioning
confidence: 99%